2022
DOI: 10.3390/electronics11081258
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-Output DC–DC Converters: Applications and Solutions

Abstract: Multiple-output DC–DC converters are essential in a multitude of applications where different DC output voltages are required. The interest and importance of this type of multiport configuration is also reflected in that many electronics manufacturers currently develop integrated solutions. Traditionally, the different output voltages required are obtained by means of a transformer with several windings, which are in addition to providing electrical isolation. However, the current trend in the development of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 103 publications
0
17
0
Order By: Relevance
“…Bidirectional converters regulate the power in both directions, while unidirectional converters have a unique power flow direction [13], [25]. In contrast, special converters include multi-port and softswitching converters for specific industrial technologies [12], [13], [32], [97], [108]- [112]. Looking specifically at the unidirectional and bidirectional converters, they can be classified into isolated converters and non-isolated converters depending on the existence of the transformer in the power circuit [11].…”
Section: A Dc-dc Convertersmentioning
confidence: 99%
See 2 more Smart Citations
“…Bidirectional converters regulate the power in both directions, while unidirectional converters have a unique power flow direction [13], [25]. In contrast, special converters include multi-port and softswitching converters for specific industrial technologies [12], [13], [32], [97], [108]- [112]. Looking specifically at the unidirectional and bidirectional converters, they can be classified into isolated converters and non-isolated converters depending on the existence of the transformer in the power circuit [11].…”
Section: A Dc-dc Convertersmentioning
confidence: 99%
“…MISO converters can be used for combining different voltage sources for EV applications while SI-MO converters are used for portable applications. Several studies present a comprehensive review related to the MPCs in various aspects such as types, design, and detailed comparison [31], [32], [18] - [19], [97], [131] - [134]. Most research trends associated with the MPCs for EV applications can be found in [32] and [18] supported by the current challenges.…”
Section: ) Multi-port Dc-dc Convertersmentioning
confidence: 99%
See 1 more Smart Citation
“…The basic flyback converter uses one active switch (MOSFET/IGBT), diode, capacitor, and transformer. Theoretically, 'k' number of batteries can be charged using a flyback converter if a transformer with 'k' number of isolated secondaries is used [103], as shown in Figure 15. Getting multiple outputs does not involve much difference in complexity, space, or cost since each additional output requires one HFT, one diode, and one capacitor.…”
Section: Potential Extension Of Existing Isolated Dc-dc Converters Fo...mentioning
confidence: 99%
“…Figure 17 shows the implementation of a forward converter with multiple winding to enable simultaneous charging of batteries. Similar to a flyback converter, the forward converter also has a power limitation of 100 W [103]. The output of the kth winding is related to the input as given by Equation (12).…”
Section: Single-switch Multi-output Forward Convertermentioning
confidence: 99%